2018
DOI: 10.1002/ijc.31636
|View full text |Cite
|
Sign up to set email alerts
|

A novel fusion gene PLEKHA6‐NTRK3 in langerhans cell histiocytosis

Abstract: Langerhans cell histiocytosis (LCH) is the most common histiocytosis with constitutive activation of the RAS-RAF-MEK-ERK (MAPKinase) cell signaling pathway. We analyzed 89 cases of BRAF and MAP2K1 mutations by Sanger sequencing, of which 18 cases showed that these two gene mutations are negative. Whole genome sequencing of suitable specimens in these negative cases revealed a translocation from the 3 intron of PLEKHA6 to the 13 intron of NTRK3 in one case. We identified that this translocation could cause a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…By comparing the clinical features of patients with MAP2K1 mutation and the BRAF V600E mutation, it was found that BRAF V600E -mutated LCH occurred earlier with a younger age of disease onset, and most of the patients had RO (especially liver) and skin involvement, while the patients with MAP2K1 mutation mostly had SS-multiple bone involvement. These results are similar to those of previous studies (Cai et al 2019).…”
Section: Discussionsupporting
confidence: 93%
“…By comparing the clinical features of patients with MAP2K1 mutation and the BRAF V600E mutation, it was found that BRAF V600E -mutated LCH occurred earlier with a younger age of disease onset, and most of the patients had RO (especially liver) and skin involvement, while the patients with MAP2K1 mutation mostly had SS-multiple bone involvement. These results are similar to those of previous studies (Cai et al 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Other variants of BRAF have been described in LCH, including in‐frame deletions, fusions and duplications, 141 together with somatic mutations of MAP2K1 which, similar to BRAF, increase phosphorylation of ERK 155 . Other genetic alterations have been associated with LCH, such as the fusion gene PLEKHA6‐NTRK3, which is also able to activate the ERK pathway 156 …”
Section: Langerhans Cell Histiocytosismentioning
confidence: 99%
“… 7 Similar to ECD, kinase fusions ( BRAF, ALK, NTRK1 ), BRAF - duplications, insertions, deletions, and rare mutations in the PI3K-AKT-mTOR pathway have been reported in LCH as well. 7 , 11 , 12 These molecular discoveries have implications for the diagnosis and management of LCH, and in conjunction with other recent studies on LCH in adults, have necessitated an update of the existing recommendations.…”
Section: Introductionmentioning
confidence: 99%